Conventional methodology of learning vocal repertoire: Voice students from Faculty of Music UiTM / Syazwan Junaidi - Junaidi, Syazwan (Faculty of Music, 2013)
This research is to investigate the Conventional Methodology of Learning Vocal Repertoire specifically for Voice students in UiTM Shah Alam, Malaysia. This research has been conducted in Faculty of Music UiTM Shah Alam with mtal 50 respondents, the respondents was a mixture of Diploma and Degree level‘ Furthermore. this research discovered the understanding learning and rote learning, this research also clarified which method of learning is more often to use and how it can contribute to the effective learning a vocal repertoire‘ In this research, 40 (100%) respondents oflen to use the rote learning and another 10 (20%) respondents often to use the understanding learning. Each methodology tremendously influenced them to learn the music differently. Due to this fact, voice students must have the learning and training processes in experienced of proper learning and education in music